Study on the mechanism of mitigating membrane fouling in MFC-AnMBR coupling system treating sodium and magnesium ion-containing wastewater - Hu, Jijing (Environmental technology, 2024)
Anaerobic Membrane Bioreactors (AnMBR) offer numerous advantages in wastewater treatment, yet they are prone to membrane fouling after extended operation, impeding their long-term efficiency and stability. In this study, a coupled system was developed using modified conductive membranes as the filtration membrane for the AnMBR and as the anodic conductive membrane in the microbial electrochemical system, with a total volume of approximately 2.57 L. The research focused on understanding the membrane fouling characteristics of the AnMBR when treating wastewater containing sodium ion (Na+) and magnesium ion (Mg2+). When the system was treating wastewater containing Na+, organic pollutants such as proteins and polysaccharides were identified as the primary causes of membrane fouling. Three experimental groups generating different electric currents exhibited extended operational times compared to the open-circuit control group, with extensions of 30, 24, and 15 days, respectively. Conversely, when treating wastewater with Mg2+, organic-inorganic composite fouling, primarily driven by Mg2+ bridging, emerged as the key challenge, with the experimental groups showing operational extensions of 5, 8, and 23 days, respectively, in comparison to the control group. Analysis of proteins and polysaccharides indicated that electric current played a crucial role in reducing organic fouling in the sludge cake layer. When treating wastewater containing Na+, the effectiveness of membrane fouling control was directly proportional to the electric current, while when treating wastewater containing Mg2+, it was directly proportional to the voltage